Pengaruh Model Team Games Tournament (Tgt) Berbantuan Media Timacase Terhadap Minat Belajar Siswa Kelas III SD Pringapus 01 - Aulia Gita Oviyana; Anni Malihatul Hawa (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to determine the effect of the Team Games Tournament (TGT) learning model assisted by TIMACASE media on students’ learning interest at SD Negeri Pringapus 01. The low level of students’ learning interest, characterized by limited attention, participation, and involvement during learning activities, requires the implementation of innovative learning strategies. This research employed a quantitative approach with a quasi-experimental method using a Nonequivalent Control Group Design. The research sample consisted of 48 third-grade students, with 24 students in the experimental class and 24 students in the control class. Data were collected using learning interest questionnaires and analyzed through descriptive statistics, normality tests, homogeneity tests, and Independent Sample t-test. The results showed that the average pretest score of the experimental class was 62.08 and increased to 84.54 in the posttest, while the control class increased from 61.42 to 72.08. The hypothesis test obtained a significance value of 0.000 < 0.05, indicating a significant effect of the TGT model assisted by TIMACASE media on students’ learning interest. Therefore, the implementation of TGT assisted by TIMACASE media can be an effective alternative to create active, enjoyable, and meaningful learning experiences for elementary school students.